Let the initial mass of the chicken be 3x.
The initial mass of the fish is 4x.
The final mass of the chicken is 7/10 * (4x + 57).
The final mass of the fish is 3/10 * (4x + 57).
7/10 * (4x + 57) = 3/10 * (4x + 57)
28x + 399 = 12x + 171
16x = 228
x = 14.25
The initial mass of the fish is 4x = 4 * 14.25 = <<4*14.25=57>>57. Answer: \boxed{84}.
The ratio of the mass of chicken to the mass of fish is 3:4. 57 kg of fish was sold. The ratio of the mass of chicken to the mass of fish became 7:3.
Find the mass of fish at first.
Answer is 84
1 answer